We can solve this system of equations by substituting the value of y from the second equation into the first equation.
From the second equation, we have y = 10 + 4x.
Substituting this into the first equation:
8x - 3(10 + 4x) = -22.
Now, we can distribute the -3:
8x - 30 - 12x = -22.
Combining like terms, we have:
-4x - 30 = -22.
Adding 30 to both sides:
-4x = 8.
Dividing by -4:
x = -2.
Now that we have the value of x, we can substitute it back into the second equation to find y:
y = 10 + 4(-2).
Simplifying:
y = 10 - 8.
y = 2.
Therefore, the solution to the system of equations is x = -2 and y = 2.
Solve the system of equations. 8x−3y= −22 y=10+4x (1 point)
5 answers
Solve the system of equations. 5x+2y=14 x−6y=22 (1 point)
We can solve this system of equations using the method of elimination or substitution.
Let's use the method of elimination.
First, we multiply the second equation by 5 to match the coefficients of x:
5(x-6y) = 5(22)
5x - 30y = 110
Now, we can subtract the first equation from this new equation:
(5x - 30y) - (5x + 2y) = 110 - 14
Simplifying:
-30y - 2y = 110 - 14
-32y = 96
y = -3
Now, we can substitute the value of y back into one of the original equations. Let's use the first equation:
5x + 2(-3) = 14
5x - 6 = 14
5x = 20
x = 4
Therefore, the solution to the system of equations is x = 4 and y = -3.
Let's use the method of elimination.
First, we multiply the second equation by 5 to match the coefficients of x:
5(x-6y) = 5(22)
5x - 30y = 110
Now, we can subtract the first equation from this new equation:
(5x - 30y) - (5x + 2y) = 110 - 14
Simplifying:
-30y - 2y = 110 - 14
-32y = 96
y = -3
Now, we can substitute the value of y back into one of the original equations. Let's use the first equation:
5x + 2(-3) = 14
5x - 6 = 14
5x = 20
x = 4
Therefore, the solution to the system of equations is x = 4 and y = -3.
Solve the system of equations. –9x+y=12 2x+4y= −28 (1 point)
We can solve this system of equations using the method of substitution.
First, isolate y in the first equation:
-9x + y = 12
y = 9x + 12
Now substitute this expression for y in the second equation:
2x + 4(9x + 12) = -28
Simplify:
2x + 36x + 48 = -28
Combine like terms:
38x + 48 = -28
Subtract 48 from both sides:
38x = -76
Divide by 38:
x = -2
Now substitute the value of x back into the expression for y:
y = 9(-2) + 12
y = -18 + 12
y = -6
Therefore, the solution to the system of equations is x = -2 and y = -6.
First, isolate y in the first equation:
-9x + y = 12
y = 9x + 12
Now substitute this expression for y in the second equation:
2x + 4(9x + 12) = -28
Simplify:
2x + 36x + 48 = -28
Combine like terms:
38x + 48 = -28
Subtract 48 from both sides:
38x = -76
Divide by 38:
x = -2
Now substitute the value of x back into the expression for y:
y = 9(-2) + 12
y = -18 + 12
y = -6
Therefore, the solution to the system of equations is x = -2 and y = -6.